Truncated partial-wave analysis of a complete experiment for photoproduction of two pseudoscalar mesons on a nucleon; Physical Review C - Nuclear Physics; Vol. 87, № 4 - Fiks (Fix) A. I. Alexander Ivanovich (2013, 2013)
Title screen